2004
DOI: 10.1046/j.0041-1132.2004.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Universal leukoreduction decreases the incidence of febrile nonhemolytic transfusion reactions to RBCs

Abstract: As our institution has increased its inventory of leukoreduced RBCs to approximately 100 percent, selective leukoreduced protocols have been discontinued. The incidence of FNHTRs has decreased significantly and the rate of allergic reactions has essentially remained unchanged. Leukoreduction is effective in decreasing FNHTRs associated with the transfusion of allogeneic RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
127
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 13 publications
11
127
1
5
Order By: Relevance
“…12 Leukoreduction of these stored units have been consistently associated with low rates of non-hemolytic febrile transfusion reactions. [13][14][15] Hebert and colleagues evaluated the impact of leukoreduction across 23 Canadian hospitals subsequent to a universal prestorage leukoreduction program. 16 Outcomes evaluated included mortality, infections, fever and antibiotic use among 14,786 patients (6,982 during a period prior to the implementation, and 7,804 after the program's implementation) who received RBC transfusions secondary to cardiac surgery, repair from hip fracture, or during their intensive care unit stay following a surgical intervention or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…12 Leukoreduction of these stored units have been consistently associated with low rates of non-hemolytic febrile transfusion reactions. [13][14][15] Hebert and colleagues evaluated the impact of leukoreduction across 23 Canadian hospitals subsequent to a universal prestorage leukoreduction program. 16 Outcomes evaluated included mortality, infections, fever and antibiotic use among 14,786 patients (6,982 during a period prior to the implementation, and 7,804 after the program's implementation) who received RBC transfusions secondary to cardiac surgery, repair from hip fracture, or during their intensive care unit stay following a surgical intervention or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of febrile non-hemolytic transfusion reactions has decreased significantly since leukoreduction has been implemented [67].…”
Section: Pro-inflammatory State After Blood Transfusionmentioning
confidence: 99%
“…8 In another study carried by Karen E et al who compared the results of incidence of FNHTRs over two time periods after introduction of universal leucoreduced PRBCs found that there was a significant difference in the incidence of FNHTRs seen between the two-time periods (0.37% in 1994 vs. 0.19% in 2001, p = 0.0008). 9 Kumar H et al also showed that after the introduction of leucodepletion of blood for thalassemics at their center, the incidence of non-haemolytic febrile transfusion reactions (NHFTR) fell from 4% in 2002 to 1% in 2003. 7 On comparing our study with the above mentioned studies we get the similar results which indicate that prestorage leukoreduction of RBCs is beneficial in reducing the incidence of FNHTRs.…”
Section: Discussionmentioning
confidence: 99%